Novel Insights into the Kallikrein–Kinin System in Fulminant Myocarditis: Physiological Basis and Potential Therapeutic Advances - Ji M; Ran X; Zuo H; Zhang Q (Dove Medical Press, 2024)
Mengmeng Ji,1,* Xiao Ran,2,3,* Houjuan Zuo,1 Qin Zhang4 1Division of Cardiology, Department of Internal Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of China; 2Department of Critical-Care Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of China; 3Department of Emergency Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People's Republic of China; 4Department of Anesthesiology, Hubei Key Laboratory of Geriatric Anesthesia and Perioperative Brain Health, and Wuhan Clinical Research Center for Geriatric Anesthesia, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of China*These authors contributed equally to this workCorrespondence: Qin Zhang, Department of Anesthesiology, Hubei Key Laboratory of Geriatric Anesthesia and Perioperative Brain Health, and Wuhan Clinical Research Center for Geriatric Anesthesia, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, 1095# Jiefang Ave, Wuhan, 430030, People's Republic of China, Tel +86-15717154768, Email qzhang8@tjh.tjmu.edu.cn Houjuan Zuo, Division of Cardiology, Department of Internal Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, 1095# Jiefang Ave, Wuhan, 430030, People's Republic of China, Tel +86-83663280, Email zuohoujuan@126.comAbstract: Fulminant myocarditis (FM) is characterized by rapid cardiac deterioration often instigated by an inflammatory cytokine storm. The kallikrein-kinin system (KKS) is a metabolic cascade known for releasing vasoactive kinins, such as bradykinin-related peptides, possessing diverse pharmacological activities that include inflammation, regulation of vascular permeability, endothelial barrier dysfunction, and blood pressure modulation. The type 1 and type 2 bradykinin receptors (B1R and B2R), integral components of the KKS system, mediate the primary biological effects of kinin peptides. This review aims to offer a comprehensive overview of the primary mechanisms of the KKS in FM, including an examination of the structural components, regulatory activation, and downstream signaling pathways of the KKS. Furthermore, it explores the involvement of the tissue kallikrein/B1R/inducible nitric oxide synthase (TK/B1R/iNOS) pathway in myocyte dysfunction, modulation of the immune response, and preservation of endothelial barrier integrity. The potential therapeutic advances targeting the inhibition of the KKS in managing FM will be discussed, providing valuable insights for the development of clinical treatment strategies. Keywords: fulminant myocarditis, Kallikrein-Kinin system, inducible nitric oxide synthase, nitric oxide, inflammatory